Bahasa Slang dalam Komunikasi Grup WhatsApp Mahasiswa Kedokteran Universitas Islam Al Azhar Angkatan 2025: Analisis Bentuk, Makna, dan Konteks dalam Kajian Sosiolinguistik - Siti Aminah; Dewi Utary (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
Slang language is a linguistic variation that develops within particular social groups to express identity and solidarity in communication. This study aims to describe the forms, meanings, and contexts of slang language used in the WhatsApp group communication of the 2025 cohort of Medical Faculty students at Universitas Islam Al Azhar. A descriptive qualitative method with a sociolinguistic approach was employed. Data were collected from WhatsApp conversations and analysed through data reduction, classification, interpretation, and conclusion drawing. The findings reveal four forms of slang: abbreviations, wordplay, terms of address, and foreign or regional vocabulary. The meanings primarily reflect invitations and refusals, while their use is closely associated with intimacy, communication efficiency, group identity, linguistic creativity, and contemporary language trends. These findings indicate that slang functions as a marker of social identity and solidarity in students' digital communication.